2020
DOI: 10.1186/s40621-020-00250-5
|View full text |Cite
|
Sign up to set email alerts
|

Child passenger safety education in the emergency department: teen driving, car seats, booster seats, and more

Abstract: Background: The leading cause of death in children less than 19 years old is motor vehicle crashes (MVC). Non-use or improper use of motor vehicle car seats significantly adds to the morbidity and mortality. Emergency department (ED) encounters provide an opportunity for caregiver education. Our objective was to determine the effect of an educational intervention on knowledge and counseling behaviors of pediatric ED nurses regarding child passenger safety (CPS). Methods: A pre/post educational intervention stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Ekundayo et al (2013) and Smola et al ( 2020) conducted similar studies using a pre-and posttest design with a CPS education intervention and showed increased nurse CPS knowledge and confidence level postintervention comparable with our study. Smola et al (2020) focused on overall pre-and postintervention knowledge, whereas Ekundayo et al (2013) also considered the demographics of the study participants and found no significant knowledge difference between age groups or ethnicities, similar to our study. Finally, one study targeted education for caregivers and showed similar outcomes to this study (Budziszewski et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Ekundayo et al (2013) and Smola et al ( 2020) conducted similar studies using a pre-and posttest design with a CPS education intervention and showed increased nurse CPS knowledge and confidence level postintervention comparable with our study. Smola et al (2020) focused on overall pre-and postintervention knowledge, whereas Ekundayo et al (2013) also considered the demographics of the study participants and found no significant knowledge difference between age groups or ethnicities, similar to our study. Finally, one study targeted education for caregivers and showed similar outcomes to this study (Budziszewski et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…Previous research describes the importance of educating clinicians on basic CPS (Ekundayo et al, 2013; Kuska & Zonfrillo, 2017; Smola et al, 2020). However, our research extends the current CPS training literature by addressing the gap of specifically targeting nurses assigned to the NICU, PICU, pediatric unit, and MBU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NYS child restraint laws have been shown to be an effective way at reducing MV injuries in children (Sun et al, 2010 ). Previous research comparing child restraints and seat belts alone for children aged 2–6 years has demonstrated that child restraint systems offer considerable safety advantage over seat belts (Macy et al, 2014 ; Smola et al, 2020 ). Child restraints are specially designed to help reduce the risk of ejection during a crash as well as to better distribute the force of the crash through stronger bones rather than soft tissues (Durbin et al, 2003 ; Elliott et al, 2006 ; Winston et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increased knowledge of CPS recommendations and practices is Standardizing Child Passenger Safety Screening in the Emergency Department: A Quality Improvement Study associated with improved confidence and frequency of providing anticipatory guidance to families (Zonfrillo et al, 2014). Morrissey et al (2016) and Smola et al (2020) reported that providers and registered nurses (RNs) who received CPS education significantly increased anticipatory guidance teaching to families and were more likely to counsel families in the areas of seat belts, front seat riders, back seat belts, graduated driver's license laws, booster seats, and MVCs.…”
mentioning
confidence: 99%